Landing on the wrong note : jazz, dissonance, and critical practice - Heble, Ajay, 1961- (Routledge, 2000)
An imaginative and passionate synthesis of form and function, Landing on the Wrong NOte goes beyond mainstream jazz criticism, outlining a new poetics of jazz that emerges not from the ivory tower but from the clubs, performances, and lives of today's jazz musicians.